1992
DOI: 10.1080/01688639208402856
|View full text |Cite
|
Sign up to set email alerts
|

The subcortical dysfunction hypothesis of memory deficits in depression: Neuropsychological validation in a subgroup of patients

Abstract: The subcortical dysfunction hypothesis of verbal learning and memory deficits in depression was evaluated by comparing the memory test profiles of unipolar depressives (n = 40) and bipolar depressives (n = 9) with those of patients with a prototypical subcortical dementia (Huntington's disease, HD), patients with a prototypical cortical dementia (Alzheimer's disease, AD), and normal controls. In a discriminant function analysis that well-differentiated the HD, AD, and normal subjects, it was found that 28.6% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
0
5

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(129 citation statements)
references
References 49 publications
7
117
0
5
Order By: Relevance
“…These findings appear consistent with a retrieval-based verbal memory profile associated with predominant subcortical brain dysfunction (Becker et al, 1995;Delis et al, 1991Delis et al, , 1995Peavy et al, 1994). In contrast, learning and memory characteristics involving forgetting, recall errors, and vulnerability to interference are more common in diseases primarily affecting cortical brain regions (e.g., Alzheimer's disease) (Delis et al, 1991;Massman et al, 1992).…”
Section: Part Ii: Cluster Analysissupporting
confidence: 71%
See 1 more Smart Citation
“…These findings appear consistent with a retrieval-based verbal memory profile associated with predominant subcortical brain dysfunction (Becker et al, 1995;Delis et al, 1991Delis et al, , 1995Peavy et al, 1994). In contrast, learning and memory characteristics involving forgetting, recall errors, and vulnerability to interference are more common in diseases primarily affecting cortical brain regions (e.g., Alzheimer's disease) (Delis et al, 1991;Massman et al, 1992).…”
Section: Part Ii: Cluster Analysissupporting
confidence: 71%
“…The CVLT is regarded as a useful tool for characterizing memory profiles associated with different neuropsychological disturbances, including Alzheimer's disease (AD), Huntington's disease (HD), and Korsakoff 's syndrome (e.g., Delis et al, 1991), HIV-1 infection (Becker et al, 1995;Delis et al, 1995;Peavy et al, 1994;White et al, 1997), depression (Massman et al, 1992), and schizophrenia (Paulsen et al, 1995). The scoring system of the CVLT allows quantification of several indices including style of learning (e.g., semantic categorization of related words), consistency of item recall across learning trials, retention of information over short and longer delays, vulnerability to interference, recall errors (e.g., intrusions), and discriminability (ability to detect target words from distracters on recognition testing).…”
Section: Introductionmentioning
confidence: 99%
“…These findings may assist in clarifying some of the uncertainties raised by previous research. A number of investigations have indicated that only some depressed individuals have memory dysfunction, but have stopped short of clearly identifying who those individuals are (Burt et al, 1995;Kindermann & Brown, 1997;Massman, Delis, Butters, Dupont, & Gillin, 1992;Veiel, 1997). The current study suggests that among veterans with symptoms of depression and/or anxiety, those experiencing high levels of coexisting depression and anxiety are more likely to have immediate and delayed memory difficulties than individuals reporting either depressive or anxious symptoms alone, or those with low levels of both.…”
Section: Discussionmentioning
confidence: 65%
“…These include the presence of subjective memory complaints (O'Connor et al, 1990;McGlone et al, 1990;Jonker et al, 1996;Schmand et al, 1997;Derousne et al, 1999;Harwood et al, 1999;Stewart et al, 2001), a strong association with microvascular white matter changes (Hickie et al, 1995) and impaired neurocognitive function (Hart et al, 1987;Massman et al, 1992;Boone et al, 1995;Lichtenburg et al, 1995;Lesser et al, 1996;Butters et al, 2000;Nebes et al, 2000;Alexopoulos et al, 2002).…”
Section: Introductionmentioning
confidence: 99%